Praktik Komodifikasi dan Kepelikan Sistem dalam Shopee Affiliates Program - Hikmatul Arifah Fitriani (Universitas Gadjah Mada, 2023)
Technological developments bring us to live an easy life. This not only disrupts human activities in the field of technology but also spreads to various other fields such as economics, politics, and social affairs. Many things that once seemed impossible, have become possible. One example is work activities which are now becoming more practical. We no longer need to go to work every day. Now work can be done from anywhere. In a work activity, we exchange the value which we have with the wages of the industry. As with work in general, the bigger value and the work effort we give will be proportional to the wages we get. So what if there is a job offer that pays well, but requires little effort? This is what is offered by Shopee Affiliates Program. We only need to recommend products by sharing affiliate links. When someone is shopping with the link then we will get a commission income. Sounds easy and quite tempting, right? This research will analyze commodification practices in Shopee Affiliates Program and how the efforts made by Shopee to control Affiliates Partner as a third party also contribute to profits for the marketplace.